Chios dicta est... et in Aegæo sita mari : historical archaeology and heraldry on Chios - Koukouni, Ioanna N., (Archaeopress Archaeology, 2021)
This work discusses the archaeology and history of the Greek island of Chios during the Byzantine and Genoese periods, focusing on Mount Amani. Harsh, remote, and poor, Mount Amani is nevertheless surprisingly rich in material for the landscape archaeologist and the student of historical topography, yet, until now, unknown in scholarly literature.